Kecemasan Matematika Siswa Indonesia: Analisis Data PISA dan Rekomendasi Strategi Pembelajaran - Lutfi Marfuah; Djamilah Bondan Widjajanti (Prodi Pendidikan Matematika STKIP Persada Khatu;istiwa Sintang, 2026)
Mathematics anxiety is one of the factors that can hinder students’ learning processes and outcomes. This study aims to analyze the level of mathematics anxiety among Indonesian students based on Programme for International Student Assessment (PISA) 2022 data, identify its contributing factors, and formulate appropriate instructional strategies to address it. This research employs a mixed methods approach with a sequential explanatory design through the analysis of PISA data, the distribution of mathematics anxiety questionnaires, and a literature review. The results indicate that the level of mathematics anxiety among Indonesian students falls within the low to moderate category, characterized by feelings of tension, nervousness, and helplessness when solving mathematics problems. The main contributing factors include lack of learning preparation, rapid delivery of instructional material, difficulty in recalling concepts or formulas, and environmental pressure. These findings suggest that mathematics anxiety is influenced not only by cognitive aspects but also by psychological and pedagogical factors. Therefore, comprehensive instructional strategies are needed, including enhancing students’ motivation and learning skills, implementing student-centered learning approaches, and creating a positive learning environment. These efforts are expected to reduce mathematics anxiety and improve the quality of mathematics learning.Keyword: PISA, Mathematics anxiety, Indonesian students, instructional strategies